ANOTHER LOOK AT THE DETERRENT EFFECT OF DEATH PENALTY - CHOE, Jongmook (Journal of Advanced Research in Law and Economics; Vol 1 No 1 (2010): JARLE Volume I Issue 1(1) Summer 2010, 2016)
There is a question whether the execution rate is appropriate to examine the deterrent effect of death penalty. Instead of using execution rate, this paper uses dummy variables to categorize states into different groups and to compare the group mean homicide rates. With US state-level panel data for the period 1995 – 2006, this paper fails to find a significant homicide-reducing effect of death penalty.
Keywords: death penalty, execution, homicide, deterrence, Dummy Variable